OCCURRENCE AND DISTRIBUTION OF PELAGIC FISH EGGS AND LARVAE IN THE CHILKA LAKE DURING THE YEARS 1964 AND 1965 - Kowtal, G V (Indian Journal of Fisheries, 2011)
The Chilka lake forms a lucrative fishing ground. The fish fauna, fisheriesand various aspects of fishery biology of the lake have received considerable attentionbut detailed investigations on fish eggs, larvae and juveniles of the lake are lacking.The occurrence and distribution of pelagic fish eggs and larvae form an importantstudy in capture fisheries management as they provide valuable informationon the spawning habits and habitats and availability of spawn in quality and quantityin time and space.In view of the proposals for foreshore reclamation of the Chilka lake the presentstudies assume added interest as they throw light on fish seed resources of someof the economic fishes. The life history studies of fishes are essential for the properunderstanding of their recruitment to fishery from time to time and for formulatingmeasures for conservation and development of fisheries.Works of Chaudhuri (1916, 1917, 1923), Hora (1920), Jones and Sujansinghani(1954), Mitra and Devasundaram (1954) and Jhingran et al. (1963) refer to thebreeding habits, eggs, larvae and juveniles of some of the fishes of Chilka lake. Jhingranand Natarajan (1966) have briefly reviewed the eggs, larvae and juveniles ofsome of the important fishes encountered in the lake. The present paper deals withthe occurrence and distribution of pelagic fish eggs and larvae of the Chilka lakeduring the years 1964 and 1965.